Nocturnal seizure and simultaneous bilateral shoulder fracture-dislocation - Sahbudin, Ilfita (BMJ Case Rep, 2016)
An otherwise fit and well 27-year-old man presented with acute onset unexplained bilateral shoulder pain, and was found to have bilateral shoulder fractures and dislocations on imaging. Although features were atypical, a nocturnal seizure causing the bilateral shoulder fractures was suspected and EEG showed features compatible with epilepsy.